A fundamental test for galaxy formation models: matching the Lyman-α absorption profiles of galactic halos over three decades in distance - Sorini, Daniele; Oñorbe, Jose; Hennawi, Joseph F.; Lukić, Zarija (The astrophysical journal, 2018)
Galaxy formation depends critically on the physical state of gas in the circumgalactic medium (CGM) and its interface with the intergalactic medium (IGM), determined by the complex interplay between inflow from the IGM and outflows from supernovae and/or AGN feedback. The average Lyα absorption profile around galactic halos represents a powerful tool to probe their gaseous environments. We compare predictions from Illustris and Nyx hydrodynamical simulations with the observed absorption around foreground quasars, damped Lyα systems, and Lyman-break galaxies. We show how large-scale BOSS and small-scale quasar pair measurements can be combined to precisely constrain the absorption profile over three decades in transverse distance . Far from galaxies, , the simulations converge to the same profile and provide a reasonable match to the observations. This asymptotic agreement arises because the ΛCDM model successfully describes the ambient IGM and represents a critical advantage of studying the mean absorption profile. However, significant differences between the simulations, and between simulations and observations, are present on scales , illustrating the challenges of accurately modeling and resolving galaxy formation physics. It is noteworthy that these differences are observed as far out as , indicating that the “sphere of influence” of galaxies could extend to approximately ∼7 times the halo virial radius. Current observations are very precise on these scales and can thus strongly discriminate between different galaxy formation models. We demonstrate that the Lyα absorption profile is primarily sensitive to the underlying temperature-density relationship of diffuse gas around galaxies, and argue that it thus provides a fundamental test of galaxy formation models.